I03 Magnetisation transfer MR imaging demonstrates degeneration of the subcortical and cortical grey matter in Huntington's disease. (16th November 2010) - Ginestroni, A; Ghelli, E; Mechi, C; Pradella, S; Romoli, A M; Mascalchi, M; Piacentini, S
Abstract : Purpose: To investigate with magnetisation transfer (MT) MR imaging the microstructural changes of the residual brain subcortical and cortical grey matter (GM) in carriers of the Huntington's disease (HD) gene and to preliminarily assess their correlation with the clinical features. Materials and methods: 15 HD gene carriers with a range of clinical severity and 15 age and sex matched healthy controls underwent MT MR imaging on a 1.5T scanner. The MT ratio was measured automatically in several subcortical and cortical GM regions (striatal nuclei, thalami and the neocortex of the frontal, temporal, parietal and occipital lobes) using FMRIB Software Library tools. Results: The MT ratio was significantly (p<0.05 with Bonferroni correction for multiple comparison) decreased in all subcortical structures but the putamen and diffusely in the cerebral cortex of HD carriers compared with controls. Close correlation was observed between the subcortical and cortical regional MT ratios and several clinical variables, including disease duration, motor disability and scores in timed neuropsychological tests. Conclusions: MT imaging demonstrates degeneration of the subcortical and cortical GM in HD carriers and might serve along with volumetric assessment as a surrogate marker in future clinical trials of HD.